Prevalence of Delayed Eruption of Permanent Upper Central Incisors at a Tertiary Hospital in Riyadh, Saudi Arabia - Mannaa Aldowsari; Faisal S. Alsaif; Mohammed S. Alhussain; Bander N. AlMeshary; Naif S. Alosaimi; Saleh M. Aldhubayb; Sakher AlQahtani (MDPI AG, 2022)
Tooth eruption is defined as the axial movement of the tooth from its site of development in the alveolar bone to its functional position in the oral cavity. A delay in eruption can directly affect the accurate diagnosis, overall treatment planning, and timing of treatment. Thus, Delayed Tooth Eruption can have a significant impact on a patient's proper health care. This study aimed to estimate the prevalence of delayed eruptions of permanent upper central incisors in Riyadh, Saudi Arabia. A retrospective study assessed panoramic radiographs of children between the ages of 6-10 years old who attended the Dental University Hospital clinics at King Saud University in Riyadh, Saudi Arabia between 2014 and 2020. The radiographs were collected and examined to detect any delayed eruption of the permanent upper central incisors. Panoramic radiographs with delayed erupted permanent upper central incisors were identified by tooth developmental stages and eruption sequence. Of the 745 radiographs, 23 (3.09%) presented at least one delayed erupted permanent upper central incisor of which boys and girls comprised 16 (69.5%) and 7 (30.4%), respectively. Retained primary teeth was the most causative factor of delayed eruption (43.4%), followed by the early loss of primary teeth (21.7%) and insufficient arch space. The present study is the first to assess the prevalence of delayed eruption of the permanent upper central incisors on a Saudi population. Boys were found to have more prevalence of delayed eruption of the permanent upper central incisors compared to girls. Clinicians should be aware of such a condition as early diagnosis of delayed eruption is essential for providing optimal dental care.